Bioequivalence of exemestane in post-menopausal females - Groenewoud, Gerhard; Nell, Andre; Potgieter, Linda; Seiler, Dan; Wettmarshausen, Christine (Arzneimittelforschung, 2010)
The bioavailability of two exemestane tablet formulations was compared in 74 healthy post-menopausal females, aged 46 to 74 years, during a laboratory-blind, randomized, two-treatment, two-period, cross-over study under fed conditions. In each treatment phase subjects received a single dose (one tablet) of 25 mg exemestane (CAS 107868-30-4). Consecutive dosing was separated by a drug-free washout period of 21 d. Following each dosing, serial venous blood samples were collected over a period of 144 h for the determination of plasma exemestane concentrations by means of a validated LC-MS/MS method. The geometric mean Cmax of exemestane for the reference and test products was 21.48 and 20.14 ng/mL, respectively. The corresponding mean AUC(0–∞) was 87.12 and 86.90 ng · h/mL. The median Tmax for both products under investigation appeared at 1.70 and 1.97 h, respectively. The test product was well tolerated and shown to be bioequivalent to the reference product with respect to all primary pharmacokinetic variables investigated.
Keywords: Aromatase inhibitor; CAS 107868-30-4; Exemestane, bioavailability, bioequivalence, pharmacokinetics; Post-menopausal females